Can I be a universal academic and stay loyal to my cultural roots? A Danish researcher reflects on the choices this entails - Høyen, Marianne (Adult Education Discourses, 2025)
To write this article, I examined my own educational journey through a series of critical lenses. My intention was to identify and share my experiences of learning to function within the dominant Anglocentric academic discourses when I grew up and worked within a very different cultural tradition, my foundational Danish heritage. I present my ‘findings’ here as a series of ‘Strands’ that I had to unpick and then re-twine to understand my story, interspersed by ‘Strategies’ – pauses where I share the processes I used to enable me to excavate my academic life with integrity and share my ideas with others – as I believe there are many academics working within Europe, and beyond, who will have encountered or be working through or around similar hurdles. There are many like me who lack the privilege that being a native English speaker bestows in a world where this is the dominant lingua franca.